2016
DOI: 10.1590/s0100-204x2016000500030
|View full text |Cite
|
Sign up to set email alerts
|

Amblyseius largoensis in controlling red palm mite under semi-field conditions

Abstract: -The objective of this work was to evaluate the efficiency of two Amblyseius largoensis (Acari: Phytoseiidae) populations in controlling Raoiella indica (Acari: Tenuipalpidae). The treatments were: release of A. largoensis from the island of La Réunion; release of A. largoensis from the state of Roraima, Brazil; and a control, without predator release. Initially, 20 predators were released per plant; three other releases were done at a rate of ten adults per plant, at 46, 135, and 156 days after the first rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
1
Order By: Relevance
“…Amblyseius largoensis, the third most numerous phytoseiid predator in association with R. indica in the present study, often has been reported in association with R. indica in the Neotropics, usually in coastal areas (Etienne & Flechtmann 2006;Rodrigues et al 2007;Roda et al 2008;Carrillo et al 2010;Hastie et al 2010;Carrillo et al 2011c;Gondim Jr. et al 2012;Moraes et al 2012;Flores-Gallano et al 2017). This predator has received the most attention as a possible candidate for practical use as biological control agent of the pest (Carrillo et al 2010;Carrillo et al 2011c;Carrillo et al 2012;Domingos et al 2012;Carrillo et al 2014;Morais et al 2016;Mendes et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Amblyseius largoensis, the third most numerous phytoseiid predator in association with R. indica in the present study, often has been reported in association with R. indica in the Neotropics, usually in coastal areas (Etienne & Flechtmann 2006;Rodrigues et al 2007;Roda et al 2008;Carrillo et al 2010;Hastie et al 2010;Carrillo et al 2011c;Gondim Jr. et al 2012;Moraes et al 2012;Flores-Gallano et al 2017). This predator has received the most attention as a possible candidate for practical use as biological control agent of the pest (Carrillo et al 2010;Carrillo et al 2011c;Carrillo et al 2012;Domingos et al 2012;Carrillo et al 2014;Morais et al 2016;Mendes et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study to evaluate the efficiency of two Amblyseius largoensis populations (La Réunion and the state of Roraima, Brazil) in controlling the invasive tenuipalpid mite, Raoiella indica , was carried out in Brazil; however, none of the populations exhibited efficacy to control the pest (Morais et al 2016 ). These findings suggested the necessity of complementary studies under conditions as close as possible to those of natural fields to imitate the natural environment for fully grown plants and to increase the predation rate.…”
Section: Biological Control Of Phytophagous Mites In Latin America: A...mentioning
confidence: 99%
“…65%). It can be a challenge for the implementation of biological control programmes, mainly using the most important natural enemy of R. indica, Amblyseius largoensis (Muma) (Acari: Phytoseiidae) (Carrillo et al 2012b;Gondim Jr et al 2012;Moraes et al 2012;Morais et al 2016). Temperature would not be a limiting factor for this predator to become established as its minimum temperature for development (Tb) of 13.5 °C is similar to that of R. indica (Galvão et al 2007).…”
Section: Discussionmentioning
confidence: 99%